Immigration and human development - Tabar, Paul (2009)
This paper takes Lebanon as a case study to examine the relationship between human development and immigration. It examines this issue from both ends: the sending and the receiving countries. The author suggests that by developing the concept of a diasporic civil society and a diasporic public sphere, a significant aspect of the relationship between human development and immigration is illuminated especially at the level of political, social and cultural capitals. The paper also argues that the double impact of the home country and that of destination has a lot to say about the influence of immigration on human development in Lebanon. In examining Australia as a destination country, the paper shows the particular impact that globalisation and September 11 have lately had on the capacity of the Lebanese migrants for human development. Finally, the paper concludes by showing the extent to which the diasporic civil society compensates for the ‘negligent’ character of the Lebanese state in the context of human development